The early changes in trunk muscle strength and disability following lumbar spine fusion - Tarnanen, Sami; Neva, Marko H.; Kautiainen, Hannu; Ylinen, Jari; Pekkanen, Liisa; Kaistila, Tiina; Vuorenmaa, Mirja; Häkkinen, Arja (Disability and rehabilitation, 2013)
Purpose: To analyze trunk muscle function pre- and postoperatively in patients undergoing lumbar spine fusion. Associations between changes in trunk muscle strength and disability were also studied. Method: A total of 114 patients undergoing lumbar spine fusion participated in the study. The flexion and extension strength of the trunk was measured preoperatively and 3 months after surgery using a strain-gauge dynamometer. Disability and pain during the past week was evaluated with the Oswestry disability index (ODI) and visual analog scale (VAS), respectively. Results: Preoperative trunk extension and flexion strength levels were 319 N and 436 N in males, respectively, and 160 N and 214 N in females, respectively. In females 3 months postoperatively, the trunk extension strength increased by 39 N (p < 0.001) and flexion by 38N (p < 0.001), whereas it remained unchanged in males. The preoperative extension/flexion strength ratio was 0.79 in females and 0.76 in males. Three months postoperatively, the strength ratio decreased to 0.66 in males (p = 0.02). The mean ODI improved by 47% and back pain decreased by 65% (both p < 0.001). The changes in the ODI correlated with changes in trunk extension (r = −0.38) and flexion (r = −0.43) strength. Conclusions: Patients undergoing lumbar spine fusion had low trunk muscle strength and strength imbalance. Back fusion surgery leads to considerable relief of pain and disability, but patients still have low trunk extension and flexion strength levels 3 months postoperatively. Therefore, there is need for a proper progressive strength training protocols to normalize back function. Implications for Rehabilitation Disability and pain decreased considerably during early recovery after lumbar fusion surgery. The changes in trunk muscle function were small and imbalances between the function of trunk extensor and flexor muscles still existed 3 months postoperatively. Back pain during straining was only weakly associated with strength values, indicating that the reasons for the low strength values are probably related to more than just pain inhibition. The correlation between the changes in trunk muscle strength and the changes in the ODI indicate that increase of muscle strength may decrease disability of these patients.